Sprint mechanics return to competition follow-up after hamstring injury on a professional soccer player: A case study with an inertial sensor unit based methodological approach - Setuain, I.; Lecumberri, P.; Izquierdo, M. (Journal of Biomechanics, 2017)
Background: The present research aimed to describe an inertial unit (IU)-based sprint mechanics evaluation model for assessing players` readiness to return to competition after suffering a grade I hamstring injury. Methods: A professional male football player (age 19 years; height 177 cm; weight 70 kg, midfielder, Spanish, 3° Division) with a grade 1 biceps femoris injury was evaluated at pre-season, at return to play after injury and at the end of the competitive season. Sprint mechanics were analyzed via the use of an inertial orientation tracker (Xsens Technologies B.V. Enschede, Netherlands) attached over the L3-L4 region of the subject`s lumbar spine. Sprint mechanics such as horizontal components of ground reaction force were assessed in both legs during sprinting actions. Findings and interpretation: Both the coefficient of the horizontal force application (SFV) and the ratio of forces (DRF) applied at increasing velocity were decreased in the injured limb compared with the contralateral healthy limb at the return to play evaluation (73% and 76% reductions, respectively) and returned to symmetrical levels at the end-season evaluation.